2010
DOI: 10.1051/dst/2009050
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of milk protein concentrate solubility using focused beam reflectance measurement

Abstract: -Milk protein concentrate (MPC) is a newly developed dairy powder with high protein content (40-90 wt%). MPC is known to have relatively poor dissolution properties, rendering traditional testing methods ineffective for characterizing their functionality. To date, various techniques have been used to quantitatively measure the properties of MPC. Mostly, they are conducted offline with considerable sample preparation that influences the reproducibility of the measurement. Here, a methodology to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…Analysis of PSD, after 90 min and 24 h rehydration, confirmed the results of numerous previous studies which reported the presence of large poorly-dispersible particles in high-protein MPCs after reasonable periods of rehydration (Fang et al, 2010(Fang et al, , 2011Mimouni et al, 2009Mimouni et al, , 2010b. In addition, it is clear that this phenomenon is not restricted to powders with >80% protein, with MPC60 and MPC70 also displaying similar behaviour.…”
Section: Dispersion Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…Analysis of PSD, after 90 min and 24 h rehydration, confirmed the results of numerous previous studies which reported the presence of large poorly-dispersible particles in high-protein MPCs after reasonable periods of rehydration (Fang et al, 2010(Fang et al, , 2011Mimouni et al, 2009Mimouni et al, , 2010b. In addition, it is clear that this phenomenon is not restricted to powders with >80% protein, with MPC60 and MPC70 also displaying similar behaviour.…”
Section: Dispersion Characteristicssupporting
confidence: 86%
“…8. Increasing the temperature of reconstitution to $50°C is common industrial practice when a dairy powder is difficult to reconstitute; however, the correlation between increased temperature and improved rehydration is often weak (Fang et al, 2010;Richard et al, 2013), as it depends on the composition, processand storage-history of the powder. A higher temperature of reconstitution resulted in a strong decrease in sediment height for MPC90 rehydrated in water (Fig.…”
Section: Effect Of Temperature and Additives On Mpc90 Solubilitymentioning
confidence: 99%
“…Another approach developed by Fang et al (2010Fang et al ( , 2011 used focused beam reflectance measurements. All these methods have managed to give insights into the process of solubility, factors and interactions involved in rehydration process and subsequently draw correlations with loss of solubility in MPC as also done by Mata et al (2011) using small angle X-ray scattering method.…”
Section: Methods Used To Study Dissolution Kinetics In Mpcmentioning
confidence: 99%
“…The second method attempted to characterize the solubility of MPC using focused beam reflectance measurements (FBRM), which provides the ability to monitor changes in chord length over time under a variety of suspension concentrations (Fang et al, 2010). A characteristic dissolution profile for different MPC powders was able to be established, but it was recognized that further investigation must be conducted to confirm FBRM as a method suitable for MPC solubility analysis, especially given that MPCs vary widely in composition and dissolution characteristics.…”
Section: Advances In Assessing Mpc Solubilitymentioning
confidence: 99%